ANALISIS PERILAKU HERDING BERDASARKAN TIPE INVESTOR DALAM KEPEMILIKAN SAHAM (Studi Kasus pada Saham LQ-45 Periode Januari 2009-Juni 2014) - Tristantyo, Rajendra Wishnu; Arfianto, Erman Denny (Diponegoro Journal of Management, 2014)
This research will analyze herding behavior based on the types of investors in Indonesian capital market 2009-2014. Investors are not only using the estimate of the prospects of investment instruments, but psychological factors also determine the investment. The presence of psychological factors can affect investment and results to be achieved. Analysis by type investor, time effect herding, impact of the transmission investor, and how behavior relation ships a cross investor.This research using method of Vector Autoregression (VAR), shares volume by using a sample of companies which listed on the stock index LQ-45 month period January 2009 to June 2014. The reason using LQ-45 index because the share of liquidity, market capitalization high, has a high-frequency trading. In this VAR Analysis model there are four method that had selected which are: VAR analysis, impulse respond function (IRF), Variance Decomposition, and Granger causality test.The results of VAR analysis shows that impact of herding behavior that issignificantly affected by a fellow investor. IRF showed a response to average shock occurred during first month, variance decomposition results show impact of behavior fellow investors responded only type of investor. Granger causality show that there is a causal relationship between type investors of foreign institutional to domestic individual, domestic institutional to foreign institutional, and domestic institutional to domestic individual relationship is going in one direction. The results four analyzes can explain existence of herding behavior in Indonesian capital market, although the effect only on a fellow investor type.